2010
DOI: 10.1103/physreve.81.050101
|View full text |Cite
|
Sign up to set email alerts
|

Kibble-Zurek mechanism and infinitely slow annealing through critical points

Abstract: We revisit the Kibble-Zurek mechanism by analyzing the dynamics of phase ordering systems during an infinitely slow annealing across a second order phase transition. We elucidate the time and cooling rate dependence of the typical growing length and we use it to predict the number of topological defects left over in the symmetry broken phase as a function of time, both close and far from the critical region. Our results extend the Kibble-Zurek mechanism and reveal its limitations. PACS numbers:The out of equil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
126
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(142 citation statements)
references
References 32 publications
13
126
2
1
Order By: Relevance
“…We also showed that non-zero sub-critical temperatures have no large effect on this initial regime. More details on this issue, as well as on the effects of a slow cooling across the critical point [55], will be given in [56].…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that non-zero sub-critical temperatures have no large effect on this initial regime. More details on this issue, as well as on the effects of a slow cooling across the critical point [55], will be given in [56].…”
Section: Discussionmentioning
confidence: 99%
“…The configuration of defects remains unchanged in time, in the statistical sense, if the spatial coordinates are scaled by this length scale, which usually grows according to a power law L(t) ∼ t 1/z . Here, z is the nonequilibrium dynamical exponent, which is in general different from the dynamical critical exponent of the phase transition that may have produced the defects in the first place [1,41]. Consider, for instance, the first-order, equal-time correlation function.…”
mentioning
confidence: 99%
“…Although the classical Kibble-Zurek mechanism (its limitations and possible extensions) is still a matter of discussion [54,55], we aim at finding new clues in experiments which could enlighten the Kibble-Zurek mechanisms from its foundations (i.e. causality and dynamical aspects of bifurcations).…”
Section: Introductionmentioning
confidence: 99%